The Relationship between Emotional Intelligence and Stress, Anxiety, and Depression among Iranian Students - Zarei 1, Fatemeh; Akbarzadeh 1, Isa; Khosravi 2*, Ahmad (Shahroud Journal of Medical Sciences, 2019)
Bckground: Entering a new environment such as university would expose students to many psychological tensions. Among students, those with higher emotional intelligence can manage their stress better in critical situations. The purpose of this study was to investigate the relationship between emotional intelligence and levels of stress, anxiety, and depression among students.Methods: This study was a cross-sectional one and the population included all students of Shahroud University of Medical Sciences. The participants were 403 students who were selected through multi-stage random sampling. Shiring Emotional Intelligence Questionnaire and Depression, Anxiety, and Stress scale (DASS-21) were used to collect data. Independent t-test, chi-square, and pearson correlation coefficient and also SPSS software were used to analyze the data.Results: The results indicated that 82.2% of the participants (n=331) had high emotional intelligence and 17.9% (n=72) had moderate emotional intelligence. The mean score of emotional intelligence was 113.5 among the participants, and levels of stress, anxiety, and depression were significantly different between two groups of students with high and medium emotional intelligence. Correlation of emotional intelligence score with stress score (r = -0.59), anxiety score (r = -0.57) and depression score (r = -0.65) indicated a reverse and significant relationship between emotional intelligence with stress, anxiety, and depression.Conclusions: According to the relationship observed between emotional intelligence and management of psychological tensions in students, it is suggested that authorities should take the necessary steps to improve students' emotional intelligence.Keywords: Anxiety, Depression, Emotional Intelligence, Stress, Students.